2013
DOI: 10.1002/sce.21092
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy‐Value Models for the STEM Persistence Plans of Ninth‐Grade, High‐Ability Students: A Comparison Between Black, Hispanic, and White Students

Abstract: Group differences in the effects of the expectancies and values that high‐ability students have for science and mathematics on plans to persist in science, technology, engineering, and mathematics (STEM) were investigated. A nationally representative sample of ninth‐grade students, the High School Longitudinal Study of 2009 (HSLS: 2009; n = 21,444) was used. The analytic sample was 1,757 (48% female, 52% male) Black (13.8%), Hispanic (26.7%), and White (59.6%) students who scored in the top 10% of their race g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
150
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(168 citation statements)
references
References 32 publications
11
150
0
7
Order By: Relevance
“…These demographic variable findings diverge with some prior research. Maltese and Tai (2011) found no effect of gender and race on personal goals while Andersen and Ward (2013) found no significant relationship of gender and subjective task values. Given that both these longitudinal studies used high-achieving college-bound sample, differences in their samples and ours may be an important part of the explanation for the differences.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These demographic variable findings diverge with some prior research. Maltese and Tai (2011) found no effect of gender and race on personal goals while Andersen and Ward (2013) found no significant relationship of gender and subjective task values. Given that both these longitudinal studies used high-achieving college-bound sample, differences in their samples and ours may be an important part of the explanation for the differences.…”
Section: Discussionmentioning
confidence: 84%
“…In DeWitt's (DeWitt et al, 2011) U.K. study, the researchers reached the conclusion that external factors such as parental influence were the primary underlying cause for similar demographic disparities. Among a racially diverse population of high achieving mathematics students, Caucasian students showed stronger motivation for science persistence over African-American students and Hispanic students (Andersen & Ward, 2013). In a contrasting study, Riegle-Crumb and King (2010) found that once K-12 academic preparation is taken into account, African-Americans are more likely to declare and persist in STEM majors.…”
Section: Race/ethnicitymentioning
confidence: 98%
“…Thus, science education should start introducing information about science-related careers already during the early stages of primary school (cf. Andersen & Ward, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Providing students with support, information and advice about career options and educational requirements, seems to be critical for increasing the utility value of school science. Information about STEM careers needs to be part of the science curricula (Andersen & Ward, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While prior research lends preliminary support for links between science identity and science achievement outcomes in college, including links between identity development processes and achievement in an introductory chemistry course (Perez et al, 2014), most extant research is limited to cross-sectional designs (Andersen & Ward, 2013; Chemers et al., 2011; Hazari, Sonnert, Sadler, & Shanahan, 2010) or examines these relations at longer time scales, such as over a year (Estrada et al, 2011) or over four years of college (Robinson, Perez, et al, 2018). Further, the relations of heterogeneity in developmental patterns of science identity with science outcomes have been specifically examined in only one prior study (Robinson, Perez, et al, 2018).…”
Section: Outcomes Related To Science Identity Trajectoriesmentioning
confidence: 99%